"My private theory is that it's all in the head": Understandings of chronic widespread pain among social workers from municipality job centers in Denmark. Issue 1 (February 2021) - Schultz, Rikke; la Cour, Peter; Kousgaard, Marius Brostrøm; Davidsen, Annette Sofie
People with chronic widespread pain (CWP) are often unfit for work, and consequently they are dependent on the municipality job center to receive social support and sickness benefits. The job center's case management is based on a social worker's assessment of the citizen's health condition. This qualitative study investigates social workers' understandings of CWP. Interviews were carried out with 12 social workers. The results showed that the participants predominantly experienced the citizens' illnesses as psychosocially mediated—referring to trauma, or a lack of meaning in the citizens' lives. Only a few participants mentioned possibilities for somatic explanations of CWP.